Expanding The Boundaries of Tolerance in Indonesia - Bono Setyo; M. Iqbal Sultan; Lelita Azaria Rahmadiva; Muhammad Syarkawi (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Conflict originates from differences that develop in society. These differences include gender, ethnicity, nationality, culture, social and economic strata, politics, religion, and beliefs, including religious sects. This study aims to determine the resolution of conflicts arising from differences in khilafah between Sunni and Wahhabi schools in East Lombok, Indonesia. This research uses a qualitative approach. Researchers obtain both primary and secondary data related to the problem by going directly to the research object (field research). Data collection techniques included observation, interviews, and documentation for qualitative data analysis in this study, using the flow model proposed by Miles and Huberman. The study's results show differences between the Sunni and Wahhabi schools of thought that developed in the village of Bebidas, Wanasaba, East Lombok, where adherents of each school hold that their respective religions' teachings and practices are authentic. This difference in understanding and practice of religion is the source of conflict. Conflict resolution is necessary to identify solutions that prevent or minimise disputes, thereby avoiding escalation to physical violence. Among other things, disputes are handled through negotiation, mediation, arbitration, and by the local village government. Additionally, efforts were made to resolve the conflict by raising the tolerance threshold between the parties. This finding also has implications for conflicts originating from other differences that develop in society. Researchers also emphasise the importance of conducting research from multiple scientific perspectives.